How Do I Manage Emotions and Develop Social Interaction? Emotional Literacy Representation of Elementary Students - Seni Apriliya; Indah Mafazatin Nailiah (Universitas Pendidikan Ganesha, 2025)
Limited reports studying emotional literacy of students were found, especially research about the ability to manage emotions and developing social interactions therefore triggered this research to be conducted. Hence, this report’s objective is to describe emotional literacy of elementary school students’ abilities in managing emotion and developing social interactions during learning activity. This research utilized qualitative approach by classroom ethnography method. The research participants were students and teachers at an elementary school in Tasikmalaya city. Data collection were gathered by observations, interviews, and documentations. Thematic data analysis was conducted by referring to emotional literacy from Steiner i.e. data reduction, data presentation, and drawing conclusion. Results of this research shown that students were able to express emotions such as happiness, anger, sadness, and being annoyed productively; most of the students express their emotions being experienced spontaneously, self-harmed and others around, some of the students were not able yet developing their social interactions; some of the students tend to have low self-confident and seldom having interaction optimally during learning process. Therefore, emotional literacy of the students, especially the ability in managing emotions and developing social interactions were not adequate yet. The implication shown that at the elementary school being investigated, massive education based on emotional literacy still not being conducted yet, hence it was recommended to conduct emotional literacy education through habituation or integrated learning activity in the school.